Role of neuroendocrine modulation and biochemistry in the sepsis in Piaractus mesopotamicus - Claudiano, Gustavo S. [UNESP]; Andrade, Sónia C.S.; Souza, Elaine C.; Yunis-Aguinaga, Jefferson [UNESP]; Coutinho, Luiz L.; Moreira, Débora K.T.; Gonçalves, Felipe C.; Mundim, Antonio V.; Marzocchi-Machado, Cleni M.; de Moraes, Flávio R. [UNESP]; Moraes, Julieta R.E. [UNESP] (Elsevier, 2020)
Sepsis is a systemic process with multifactorial pathophysiology that affects most animal species. It is responsible for high rates of morbidity and mortality. This work aimed to study the biochemical and neuroendocrine changes of the sepsis process in Piaractus mesopotamicus after Aeromonas hydrophila inoculation analyzing changes in blood leukocyte and differences in neuroendocrine-biochemical modulation using RNA-seq. Fish showed hypercortisolemia, inhibition of glucose absorption, followed by hypocortisolemia and then hyperglycemia. Thyroid hormones (T3 and T4) showed immediate decrease in serum and T4 increased 6 h post-inoculation (HPI). Sepsis-induced hormonal alterations triggered changes in the metabolic pathways increasing protein and lipid catabolism, use of transient anaerobic glycolysis and liver injury. A reference transcriptome was constructed based on blood leukocytes from P. mesopotamicus. The assembly resulted in total 266,272 contigs with a N50 of 2786 bp. There was a reorganization of plasma membrane of leukocytes at the beginning of the septic process with increased expression of neuroendocrine receptors and with continuous flow of neurotransmitters, hormones and solutes with compensatory regulation at 6 HPI. Three and nine HPI seemed to be critical, the expression of a number of transcription factors was increased, including the modulatory DEGs related to glucocorticoid and thyroid hormones induced and suppressed (FDR < 0.05). Neuroendocrine modulation can regulate leukocytes and biochemical parameters of peripheral blood, being important sources for the study of the pathophysiology of sepsis. These finding highlights the importance of further studies focusing on biochemical-neuroendocrine changes in blood leukocytes and systemic sepsis.
Keywords: Aeromonas hydrophila; Hormones; Leukocytes; Pacu; RNA-seq